Water Quality Management of Lontar Village Coastal Waters, Banten - Ani Rahmawati; Dini Surilayani (JURNAL PERIKANAN DAN KELAUTAN, 2017)
The coastal waters of Lontar Village is located in Tirtayasa District, Banten. The coastal waters of Lontar Village is also used for fishing activities that become the livelihood of the surrounding community. Communities around the coast of Lontar village dispose of household waste directly into the waters so that the waters become dirty. The existence of these activities can cause the condition of the waters to decrease even can lead to contamination. Decrease in water conditions will affect the living biota inside. Waters quality can be determined by measuring physical, chemical, biological and heavy metal parameters. Physical parameters include brightness, turbidity, and temperature. Chemical parameters are salinity, pH, dissolved oxygen, nitrate, phosphate, BOD, TSS. The biological parameter is total coliform. The parameters of heavy metals are lead and copper. The purpose of this study is to analyze the quality of coastal waters of Lontar Village based on physical, chemical, biological and heavy metal parameters. The results showed that most of the parameters of water quality (physics, chemistry, biology and heavy metals) are still in accordance with the value of water quality standards (Decree of the Minister of Environment No. 51 of 2004) only the value of lead metals exceeding the standard quality. It must be overcome so as not to disrupt the life of biota in the waters. Management that can be done is utilize aquatic biota that can absorb heavy metal content such as green shell (shell should not be consumed), reducing oil spilled from the activityof motor boats (giving box shelter under motor boat engines so that oil does not directly spill into the waters).